Stratejik finansal yönetiminde teminat mektupları ve teminat (standby) akreditiflerinin rolü - Meral, Yurdagül (İstanbul Ticaret Üniversitesi, 2019)
Her geçen gün artan küresel rekabetin sonucu olarak stratejik finansal yönetimin önemi de artmıştır. Bu çalışmada, uluslararası ticaretin finansmanında çok önemli bir rolü olan teminat mektupları ve teminat akreditifleri incelenmiştir. Teminat mektupları ve teminat akreditif türleri açıklanmıştır. Teminat mektupları ve teminat akreditifleri farklı uluslararası kurallara tabi olup, söz konusu uluslarası kurallar arasındaki benzerlikler ve farklılıklar açıklanmıştır. Teminat mektubu veya teminat akreditifi kullanımı arasındaki uygulamada farklılıklar, hangisinin, ne zaman kullanılması gerektiği ve uluslararası ticarette karşılaşılan olası riskler ve teminat mektupları ve teminat akreditiflerinin kullanımında nelere dikkat edilmesi gerektiği belirtilmiştir. Sonuç olarak teminat mektubu veya teminat (standby) akreditifin her ikisinin de kullanılabileceği, önemli olan uluslararası ticaret risklerinin azaltılması için tüm tarafları koruyan ICC Uluslararası Kurallarına uygun olarak süreçlerin yönetilmesidir.

With the increasing of global competition the importance of strategic management of finance has also increased. The letter of guarantees and standby letter of credits which have an important role in international trade have been investigated in this study. The types of letter of guarantees and standby letter of credits are defined. Letter of guarantees and standby letter of credits are subject to different international rules. The differences and similarities between international rules of letter of guarantees and standby letter of credits are defined. The difference between letter of guarantees and standby letter of credits processes are explained. The potential risks of international trade and the points to be taken into consideration while using letter of guarantees and standby letter of credits are defined. As a result, both letters of guarantee and standby letters of credit can be used, as long as the process is managed under protection of ICC international rules, which protects all parties.
Strategic finance management and role of letters of guarantees and standby letters of credit
Keywords: Stratejik Finans Yönetimi; Teminat Mektupları; Teminat (Standby) Akreditifleri; Kontrgaranti; Teyitli Teminat Akreditifi; Strategic Finance Management; Letters of Guarantee; Standby Letters of Credit; CounterGuarantees; Counter-Standby; Confirmed Standby Letter of Credit